Peningkatan Pengetahuan Masyarakat Tentang Label Gizi Pada Kemasan Makanan - Achmad Hilal; Nurul Aisyiyah Puspitarini; Djunaedi Djunaedi; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Nutrition labels on food packaging are an important source of information for consumers in choosing healthy and safe foods. However, the public's lack of understanding of nutrition label information leads to errors in food product selection, potentially increasing the risk of non-communicable diseases such as obesity, diabetes mellitus, and hypertension. This Community Service activity aims to increase public knowledge and awareness regarding nutrition labels on food packaging to support healthy food consumption behaviors. Implementation methods included educational outreach, interactive discussions, simulations of reading nutrition labels, and evaluation using pre- and post-tests. The results of the activity showed a significant increase in public knowledge regarding nutrition label components, serving sizes, and nutrient content of packaged food products. This education is expected to encourage the public to make wiser food choices and support efforts to prevent non-communicable diseases.